Experimental Student’s Worksheet with Scientific Approach for Student Grade X Semester I SMA/MA - Kenny Winas Sopranda; Lufri Lufri; Rahmawati Darussyamsu (Bioeducation Journal, 2019)
The curriculum 2013 emphasize the learning with scientific approach. The experiment is the best studying activity to develop the student’s skills and processes because involve five approaches. One of the supporting tools used in an experiment is a student’s worksheet as the guidance. Based on this need, the research was conducted to yield the valid and practical experimental student’s worksheet with scientific approach for senior high school student grade X semester 1. This research utilised the 4-D (four-D) development models which are consist of 4 steps; defining, designing, and developing. The defining step including on pre-analysis and post-analysis, students analysis, and assignment analysis. The designing step was conducted to designed the experiment’s worksheet with scientific approach. In the developing step, the validity of worksheet was examined by 5 validator and practicality test by 2 teachers and 31 students grade X of MAN 1 Padang. The primary data obtained from validity and practicality questionnaire were analysed with descriptive analysis. It can concluded that the student’s worksheet of experiment with scientific approach which have developed for students grade X semester 1 have the very valid and practical criteria.